Gambaran Pengetahuan dan Sikap Wanita Usia 48–55 Tahun Tentang Menopause di Desa Weru RT 02 RW 05 Weru Sukoharjo Tahun 2015 - Ilafi Rumaisya Nursyi (Universitas Airlangga, 2018)
Women feel anxious when facing menopause, so many simple problems become so big and can even make a woman desperate. The menopausal phase is usually preceded by a premenopausal phase occurring at an age between 48–55 years. The attitude of women in the face of changes in the menopause is influenced by their knowledge. The purpose of this study was to know the description of knowledge and attitude of women aged 48–55 years about menopause in the Village Weru RT 02 RW 05, Sukoharjo. Descriptive research design with cross sectional approach. Research population of all women aged 48–55 years amounted to 44 people in Weru Village in April 2015. Using Sampling Purposive Sampling technique, 36 respondents can be sampled from the entire population. Data collection tools are questionnaires. Data analysis using univariate analysis of knowledge using percentage and attitude using scale range. The results of knowledge of women are on the category enough with the number of respondents 22 (61.2%). This can be seen that the knowledge of respondents about the majority of menopause already in the category enough even between the respondents are knowledgeable and less comparable. The desired expectations of the majority are experienced well but the results have not been as expected. While most women have enough attitude of 21 (58.3) categories less 8 respondents (22.3%) and minority in good category of 7 respondents (19.4). There are several factors that affect the knowledge and attitude of women 48–55 years in the face of changes in menopause.